Analysis of Several PLA2 mRNA in Human Meningiomas - Yves Denizot; Rafael De Armas; Karine Durand; Sandrine Robert; Jean-Jacques Moreau; François Caire; Nicolas Weinbreck; François Labrousse (Hindawi Limited, 2009)
In view of the important oncogenic action of phospholipase A2(PLA2) we investigated PLA2 transcripts in human meningiomas. Real-time PCR was used to investigate PLA2 transcripts in 26 human meningioma tumors. Results indicated that three Ca2+-dependent high molecular weight PLA2 (PLA2-IVA, PLA2-IVB, PLA2-IVC), one Ca2+-independent high molecular weight PLA2 (PLA2-VI) and five low molecular weight secreted forms of PLA2 (PLA2-IB, PLA2-IIA, PLA2-III, PLA2-V, and PLA2-XII) are expressed with PLA2-IVA, PLA2-IVB, PLA2-VI, and PLA2-XIIA as the major expressed forms. PLA2-IIE, PLA2-IIF, PLA2-IVD, and PLA2-XIIB are not detected. Plasma (PLA2-VIIA) and intracellular (PLA2-VIIB) platelet-activating factor acetylhydrolase transcripts are expressed in human meningiomas. However no difference was found for PLA2 transcript amounts in relation to the tumor grade, the subtype of meningiomas, the presence of inflammatory infiltrated cells, of an associated edema, mitosis, brain invasion, vascularisation or necrosis. In conclusion numerous genes encoding multiples forms of PLA2 are expressed in meningiomas where they might act on the phospholipid remodeling and on the local eicosanoid and/or cytokine networks.